Effect of supportive supervision on the process of indenting and stock management by senior nursing ward in-charges at a tertiary care hospital in Garhwal region of Uttarakhand, India - Mukesh Shukla; Tumul Nandan; Chandra Mohan Singh Rawat; Daulat Singh (Wolters Kluwer Medknow Publications, 2023)
Introduction: The duties of nursing administration include tasks such as placing orders, conducting regular checks on ward supplies, and ensuring regular updation of the stock register. This study assesses the effect of a supportive supervision strategy on the process of indenting and stock management by senior nursing ward in-charges and the barriers faced by them during the discharge of this duty. Methods: A cross-sectional study with mixed-method approach was conducted. Senior nursing officers were administered structured questionnaires and in-depth interviews for the quantitative and qualitative approaches, respectively. Quantitative analysis was done using statistical software and qualitative content analysis was done manually for the audio recorded and transcribed in-depth interviews. Results: The availability, legibility, accuracy, completeness, chronology, continuity, timeliness, safety, etc., of records, saw improvements on successive follow-up visits. On analyzing the in-depth interviews, administrative and management issues such as constantly changing personnel, unsystematic handover process, and problems related to supply chain and disposal came up. Work-related issues, such as lack of training, workload pressure, as well as staff-related and personal issues, were also identified. Conclusion: Transfers of designated senior nursing ward in-charges should be avoided if possible. In case done, the process of proper charge transfer should be followed. Issues such as the lengthy process of indenting and lack of training of nursing staff should be addressed. Incentivizing such work should be encouraged along with increasing autonomy for handling wards by senior nursing officers. Communication with all the stakeholders should be improved.